What Shapes CEFR Implementation in Arabic Language Education? A Systematic Review of Enablers and Constraints - Nadia Arrifqi; Amanda Putri; Nabila Izzatul Ufairah; Wardah Nailah El-Izzah Atulolon; Slamet Daroini (Institut Agama Islam Negeri Curup, 2026)
This study aims to examine the factors that support and hinder the implementation of the Common European Framework of Reference (CEFR) in Arabic language education. Although the adoption of CEFR has expanded significantly, its implementation remains uneven due to variations in institutional readiness, curriculum alignment, and teacher competence. While numerous studies have discussed CEFR-based materials, assessment, or pedagogy, existing research remains fragmented, and no comprehensive synthesis has mapped the enabling and constraining factors influencing CEFR implementation in Arabic language education. This study addresses this gap by systematically reviewing research published between 2018 and 2025 to identify (1) the key conditions that support CEFR adoption and (2) the major obstacles that hinder its effectiveness in Arabic language learning. Employing a Systematic Literature Review (SLR) approach following PRISMA procedures, the study analyzed selected articles through NVivo-assisted thematic coding to generate an integrated conceptual pattern of enablers and constraints. The findings indicate that successful CEFR implementation is supported by curriculum alignment with CEFR descriptors, teacher readiness, availability of CEFR-based materials, technological integration, and high learner motivation. Conversely, curriculum misalignment, limited teacher proficiency, insufficient materials, weak institutional support, and sociocultural barriers significantly restrict implementation outcomes. These findings provide an evidence-based foundation for the development of CEFR-informed policies, curricula, and pedagogical practices in Indonesia and the broader Southeast Asian context.